A comprehensive model of project team technical performance. Issue 7 (October 2016) - Liu, Wen-Hsing; Cross, Jennifer A.
Abstract: Project teams are commonly used within organizations and have been widely studied. Yet, there is still no consensus on how to define project team success and which factors contribute most strongly to success. This study sought to develop an initial, comprehensive model of project team technical performance, using a diverse sample of 133 teams, and employing regression analysis and structural equation modeling. Effectiveness, efficiency, and innovation were found to be the primary dimensions of technical performance. Each was predicted by a different set of factors, with few factors predicting multiple dimensions. Management support, cooperation, and communication were positively related to effectiveness ; efficiency was positively related to goal clarity, cooperation, and team harmony, but negatively related to team diversity ; and, innovation was positively associated with knowledge/skill and cohesion, but negatively associated with team harmony . Future research should identify additional influential factors and further explore the relationships found in this study. Highlights: Technical performance is multi-dimensional (effectiveness, efficiency, innovation). Communication and cooperation are key to effectiveness. Goal clarity and cooperation promote efficiency but functional diversity impedes it. Lack of task conflict (team harmony) benefits efficiency at the cost of innovation. Innovation increases with team knowledge and skills and cohesiveness.